Macrophages and Associated Ligands in the Aged Injured Nerve: A Defective Dynamic That Contributes to Reduced Axonal Regrowth - Stratton, Jo Anne; Eaton, Shane; Rosin, Nicole L.; Jawad, Sana; Holmes, Alexandra; Yoon, Grace; Midha, Rajiv; Biernaskie, Jeff (Frontiers in Aging Neuroscience, 2020)
Regenerative capacity of injured peripheral nerves is diminished with aging. To identify factors that contribute to this impairment, we compared the immune cell response in young versus aged animals following nerve injury. First, we confirmed that macrophage accumulation is delayed in aged injured nerves which is due to defects in monocyte migration as a result of defects in site-specific recruitment signals in the aged nerve. Interestingly, impairment in both macrophage accumulation and functional recovery could be overcome by transplanting bone marrow from aged animals into young mice. That is, upon exposure to a youthful environment, monocytes/macrophages originating from the aged bone marrow behaved similarly to young cells. Transcriptional profiling of aged macrophages following nerve injury revealed that both pro- and anti- inflammatory genes were largely downregulated in aged compared to young macrophages. One ligand of particular interest was macrophage-associated secreted protein (MCP1), which exhibited a potent role in regulating aged axonal regrowth in vitro. Given that macrophage-derived MCP1 is significantly diminished in the aged injured nerve, our data suggest that age-associated defects in MCP1 signalling could contribute to the regenerative deficits that occur in the aged nervous system.